Interpersonal assertiveness: Inside the balancing act. Issue 6 (June 2017) - Ames, Daniel; Lee, Alice; Wazlawek, Abbie
Abstract: Whether in everyday disagreements, bargaining episodes, or high‐stakes disputes, people typically see a spectrum of possible responses to dealing with differences with others, ranging from avoidance and accommodation to competition and aggression. We believe people judge their own and others' behaviors along this dimension, which we call interpersonal assertiveness, reflecting the degree to which someone stands up and speaks out for their own positions when they are faced with someone else who does not want the same outcomes. In this article, we review long‐standing and recent scholarship to characterize the curvilinear consequences of assertiveness (both "too little" and "too much" can be problematic). We consider the sources of accommodating and assertive behavior, such as motivations, expectancies, and failures of self‐regulation. We also examine ways in which people can assert themselves effectively, ranging from making precise offers in negotiations to employing rationales as part of their proposals. We conclude by noting promising directions for future research.